Asuhan Kebidanan Fisiologis Holistik Neonatus dengan Perawatan Tali Pusat Terbuka - Fajrin, Dessy Hidayati; Namira, Nurhaya Sarah Syafa (Politeknik Negeri Madura, 2023)
Cord care is an attempt to prevent cord infection and a simple nursing measure. Open umbilical cord care helps drying the umbilical cord more. The purpose of this study was to perform holistic physiological midwifery care for neonates with open umbilical cord care. This research was conducted using descriptive qualitative with a case study approach and field observation of Mrs.Y at PMB Marfuah, Sanggau Regency. The result obtained was that the baby's umbilical cord was detached on day 4 using open cord care. The conclusion is that open cord care will accelerate the detachment of the umbilical cord in neonates. It is recommended that PMB Marfuah apply holistic physiological midwifery care for neonates with open umbilical cord care because it is considered more effective than closed sterile gauze cord care.